Waqoi’ Wa Ahdatsu Riwayah ‘Bishad Shindhu’ (Muhitu al-Huzni) Lil Adib al-Banghli Mir Musharraf Husain: Dirosah Aqdiyah - Muhammad Nure Alam (Indonesian Journal of Arabic Studies, 2020)
Abstract:This research aims to demonstrate the importance of creed in human life. The creed is one of the pillars upon which the legislation of divine and non-divine religions relies. Most people act according to their beliefs and religious affiliations. The righteousness of people reflects through their beliefs and integrity of thinking. In this research, based on the analytical descriptive method, we have explored some of the creedal issues of Bangladeshi Muslims mentioned in the famous Bengali-Islamic novel "Bishad Shindhu (Ocean of Sadness)" written by Mir Musharraf Husain. Reasoning from the Qur'an and Sunnah have been applied to these issues to reach a conclusion of the study. It is observed that the biggest disagreement among people has occurred due to creedal differences as certain matters can be injected into peoples creed which they believe in. Therefore, Allah the Almighty sent all the prophets and messengers who called to the true belief, the primary goal of creating mankind and the jinn. This can only be achieved by confirming the worship of Allah alone. The acceptance of worship and deeds depends on an individuals intention. While a pure creed validates every deed, the corrupted creed invalidates all activities to be void. That is why, our Prophet Muhammad worked thirteen years in Macca to call to worship Allah alone and to establish the true belief amongst mankind. This research has established that the creed of the novelist, Mir Musharraf Husain, is a Shiite faith, which is not compatible with the true religion of Islam.